2015
DOI: 10.1007/s00134-015-3987-7
|View full text |Cite
|
Sign up to set email alerts
|

Respective impact of lowering body temperature and heart rate on mortality in septic shock: mediation analysis of a randomized trial

Abstract: The time spent with a temperature below 38.4 °C was independently associated with patient's outcome and explained 73% of the effect of the randomization on the day 14 mortality. Heart rate lowering was not a mediator of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
0
18
1
2
Order By: Relevance
“…Data from critically ill patients in general are available. We reviewed the literature and identified 12 RCTs (1785 patients) that examined the effect of fever control in the critically ill population, excluding neurological indication for temperature control [160][161][162][163][164][165][166][167][168][169][170][171]; active temperature management (pharmacologic or non-pharmacologic) did not reduce the risk of death (RR 1.03, 95% CI 0.81-1.31), ICU length of stay (MD − 0.07 days, 95% CI − 0.70-0.56), but it was effective in reducing body temperature (MD − 0.36 °C, 95% CI − 0.42 lower to − 0.29). Given the safety of acetaminophen and lack of harm in the body of evidence, increasing patient comfort through fever management maybe important.…”
Section: Rationalementioning
confidence: 99%
“…Data from critically ill patients in general are available. We reviewed the literature and identified 12 RCTs (1785 patients) that examined the effect of fever control in the critically ill population, excluding neurological indication for temperature control [160][161][162][163][164][165][166][167][168][169][170][171]; active temperature management (pharmacologic or non-pharmacologic) did not reduce the risk of death (RR 1.03, 95% CI 0.81-1.31), ICU length of stay (MD − 0.07 days, 95% CI − 0.70-0.56), but it was effective in reducing body temperature (MD − 0.36 °C, 95% CI − 0.42 lower to − 0.29). Given the safety of acetaminophen and lack of harm in the body of evidence, increasing patient comfort through fever management maybe important.…”
Section: Rationalementioning
confidence: 99%
“…The mortality outcome was similar. In a post hoc analysis, it was confirmed that temperature control was a main mediator of early mortality [ 28 ]. The benefits of cooling could be explained by specific patients’ profiles and the cooling strategy used.…”
Section: Should We Treat Pyrexia?mentioning
confidence: 99%
“…It is known that the fever response may be dangerous for patients suffering from cardiopulmonary diseases or sepsis, which can enhance neurological damage, cerebral edema, cardiac ischemia and tissue hypoxia (7) . Therefore, it should be taken into consideration that with the subsequent increase in oxygen consumption due to fever, the respiratory quotient and the cardiac output add a significant load on the clinical status of critically ill patients who may be unable to have their compensatory mechanisms stimulated for the increased metabolic demand (14) . Thus, the use of physical methods for cooling the body temperature often occurs in attempt to reduce clinical complications, which confers benefits to antipyretic therapy of hospitalized patients in the ICU (7,15) .…”
Section: Discussionmentioning
confidence: 99%